Evaluating the effect of Dovitinib, a potent non-selective FGFR inhibitor, on oligodendrocytes in vitro - Dentzien, Niklas; Justus Liebig University Giessen (My University, 2022)
Several recent studies indicate a crucial and most likely detrimental role of fibroblast growth factors (FGF) and their receptors (FGFR) in the field of demyelinating diseases including multiple sclerosis. Despite the large field of physiological FGFR functions in development and homeostasis, knockout of these receptors ameliorated the clinical course of animals in demyelinating disease models. Given these new insights into pathophysiology of demyelinating diseases we claimed that medicated FGFR blocking in vitro would positively influence myelination and neuroprotection. While the mentioned animal models show the importance of FGF/FGFR signals for demyelinating diseases, the distinct mechanisms, especially after their inhibition, remain unclear. To evaluate these mechanisms on a cellular level in our study we treated OLN- 93 oligodendrocytes with the unselective FGFR inhibitor Dovitinib and examined the expression of downstream signals, myelin proteins and neuroprotective agents as well as the morphological development. In accordance with our hypothesis, OLN-93 cells treated with Dovitinib showed a more complex phenotype accompanied by a higher expression of myelin proteins as well as BDNF and TrkB. Further changes could be seen for FGF/FGFR downstream signals where the expression of pAkt and pERK was reduced in cells treated with Dovitinib. Despite a lower proliferation and some cytotoxic effects of Dovitinib treatment we still assessed these changes of protein expression patterns as beneficial considering overall aspects of myelination and neuroprotection. Given the complexity of multiple sclerosis as an autoimmune disease, there is a variety of factors to be considered when discussing the influence of FGF/FGFR as a circumscribed signalling pathway. To further evaluate the effects of these in vivo influences on myelination there is a need for additional in vivo studies. Regarding our in vitro results with increased myelin proteins as well as neuroprotective agents and recent studies we do, however, consider the inhibition of FGF receptors a promising approach in future therapy of multiple sclerosis.
Keywords: ddc:610